Genetic bases of C7 deficiency: systematic review and report of a novel deletion determining functional hemizygosity - Balduit, Andrea; Bianco, Anna Monica; Mangogna, Alessandro; Zicari, Anna Maria; Leonardi, Lucia; Cinicola, Bianca Laura; Capponi, Martina; Tommasini, Alberto; Agostinis, Chiara; d’Adamo, Adamo Pio; Bulla, Roberta (Frontiers in Immunology, 2023)
Primary complement system (C) deficiencies are rare but notably associated with an increased risk of infections, autoimmunity, or immune disorders. Patients with terminal pathway C-deficiency have a 1,000- to 10,000-fold-higher risk of Neisseria meningitidis infections and should be therefore promptly identified to minimize the likelihood of further infections and to favour vaccination. In this paper, we performed a systematic review about clinical and genetic patterns of C7 deficiency starting from the case of a ten-year old boy infected by Neisseria meningitidis B and with clinical presentation suggestive of reduced C activity. Functional assay via Wieslab ELISA Kit confirmed a reduction in total C activity of the classical (0.6 % activity), lectin (0.2% activity) and alternative (0.1% activity) pathways. Western blot analysis revealed the absence of C7 in patient serum. Sanger sequencing of genomic DNA extracted from peripheral blood of the patient allowed the identification of two pathogenetic variants in the C7 gene: the already well-characterized missense mutation G379R and a novel heterozygous deletion of three nucleotides located at the 3’UTR (c.*97delTTC). This mutation resulted in an instability of the mRNA; thus, only the allele containing the missense mutation was expressed, making the proband a functional hemizygote for the expression of the mutated C7 allele.